CD146-HIF-1α hypoxic reprogramming drives vascular remodeling and pulmonary arterial hypertension - Yongting Luo (Nature Portfolio, 2019)
Vascular remodelling contributes to the development of pulmonary hypertension (PH). Here Luo and colleagues find that increases in CD146 levels drive vascular remodelling in PH through a cross-talk with hypoxia inducible factor (HIF) signalling, and show that inhibition of CD146 can attenuate disease progression.